Short-term effects of olive-pomace-based conditioners on soil aggregation stability - Royer, Ana Caroline (2024)
Mediterranean agriculture asks for sustainable strategies to prevent actual soil organic matter decline rates. Composting agri-food by-products for application in farmland, besides contributing to a circular economy at regional or local scales, may improve soil resistance to physical degradation. Aggregate stability (AS) is a crucial property for building up such resistance. Olive pomace is an abundant by-product of the olive oil industry that may be valorized through composting. This study aimed to assess the influence on AS of olive-pomace-based composts (OPC) applied to a sandy loam Leptosol and a clay loam Fluvisol. To assess the effects of compost characteristics on AS, three OPCs resulting from different olive pomace proportions in the composting raw material (44, 31, and 25% by volume) were applied to aggregate samples in three doses (10, 20, and 40 t.ha−1, plus control) with fine and coarse grain sizes. Controlled laboratory conditions subjected samples to daily wetting-drying cycles during a 30-day experiment. AS was measured by wet sieving. OPC application significantly increased AS in the Leptosol amended with fine (+15% vs. control) and coarse (+19%) grain-size compost. In well-aggregated Fluvisol, amendment induced a significant increase in AS only in the compost coarse grain size (+12%). The application dose significantly affected AS, with 10 t.ha−1 being the best-performing dose. OPC applications in weakly aggregated soils are seemingly an encouraging soil management practice for improving soil resistance to physical degradation and reducing soil organic matter decline rates in Mediterranean farmland.